A novel Real-Time Continuous Fuzzy Fault Tree Analysis (RC-FFTA) model for dynamic environment. (15th November 2016) - Senol, Yunus Emre; Sahin, Bekir
Abstract: The purpose of this study is to provide a real-time continuous fuzzy fault tree analysis model for dynamic environment to prevent undesired events in the complex, vague, complicated, and uncertain systems. In fault tree analysis methods, occurrence probability of an undesired event (i.e. marine accidents) is computed by using statistical, extrapolation, and expert judgement methods . In the proposed method, instant data is received by sensors, run through the algorithms, and the probabilities of risk occurrence are computed continuously. Real-time sensor systems (Automatic radar plotting aid radar, bridge navigational watch alarm system, etc.) of a ship are used to validate this model by analysing the fault trees of collision and grounding. The tests prove that this model is successful for handling the trade-offs and providing continuous improvement. Highlights: Conventional FFTA based risk analysis approaches require crucial improvements. This study deals with Real Time Continuous Fuzzy Fault Tree Analysis (RC-FFTA) method. RC-FFTA is proposed to monitor real-time continuous risk levels of complex systems. Two real cases are performed and risks of collision and grounding are observed. Proposed model is beneficial for all risky dynamic systems including maritime domain.